Eficacia de la terapia de aceptación y compromiso sobre la depresión en pacientes adultos - Barco Chrem, Rodrigo (2021)
Depression is a limiting disorder that imposes a socio-economic and emotional burden on patients and society in general. From the cognitive-behavioral approach, depression is conceived as the result of irrational thoughts, leading people to perceive reality in an idiosyncratic way and distorting their perception. Acceptance and commitment therapy (ACT) has gained interest in clinical psychology for the treatment of depression. ACT seeks that patients learn to re-conceptualize avoided stimuli in an adaptive way. The aim of the following review was to identify the effectiveness of acceptance and commitment therapy for the treatment of depression in adults. For this, a search was carried out in the Scopus and EBSCOhost databases. Studies that met the inclusion and exclusion criteria (n = 7) were chosen to analyze. Differences were found in terms of results, although there was mostly a large effect size regarding the efficacy of ACT on depression. The results indicate that ACT is effective for the treatment of depression in adults, being reliable for the reduction of depressive symptoms and an increase in the quality of life.